Mejora en el proceso de elaboración y gestión de los pronósticos de la demanda en una empresa dedicada a la venta de productos de belleza - Gordillo Cerrutti, Rodrigo (2016)
This investigation begins with a challenge posed by the firm in which the study has been conducted on the team responsible for the supervision of its demand forecasts. Based on the supposition that forecast errors affect the service-level given to customers, an improvement of the forecasting process to reduce forecast error in 10 percentage points and bring concrete economic benefits was requested.